The Role of Friends in the Opioid Epidemic - Effrosyni Adamopoulou; Jeremy Greenwood; Nezih Guner; Karen A. Kopecky (Institute of Labor Economics (IZA), 2024)
The role of friends in the US opioid epidemic is examined. Using data from the National Longitudinal Survey of Adolescent Health (Add Health), adults aged 25-34 and their high school best friends are focused on. An instrumental variable technique is employed to estimate peer effects in opioid misuse. Severe injuries in the previous year are used as an instrument for opioid misuse in order to estimate the causal impact of someone misusing opioids on the probability that their best friends also misuse. The estimated peer effects are significant: Having a best friend with a reported serious injury in the previous year increases the probability of own opioid misuse by around 7 percentage points in a population where 17 percent ever misuses opioids. The effect is driven by individuals without a college degree and those who live in the same county as their best friends.
Keywords: C26; D10; I12; J11; 330; opioid; peer-group effects; friends; instrumental variables; Add Health; severe injuries